Streptozotocin-Treated High Fat Fed Mice: A New Type 2 Diabetes Model Used to Study Canagliflozin-Induced Alterations in Lipids and Lipoproteins - Yu, Tian; Sungelo, Mitchell J; Goldberg, Ira J; Wang, Hong; Eckel, Robert H (Hormone and Metabolic Research, 2017)
The pharmacological effects of type 2 diabetes (T2DM) medications on lipoprotein metabolism are difficult to assess in preclinical models because those created failure to replicate the human condition in which insulin deficiency is superimposed on obesity-related insulin resistance. To create a better model, we fed mice with high fat (HF) diet and treated the animals with low dose streptozotocin (STZ) to mimic T2DM. We used this model to evaluate the effects of canagliflozin (CANA), a drug that reduces plasma glucose by inhibiting the sodium-glucose transporter 2 (SGLT2), which mediates ~90% of renal glucose reabsorption] on lipid and lipoprotein metabolism. After 6 weeks of CANA (30 mg/kg/day) treatment, the increase in total plasma cholesterol in HF-STZ diabetic mice was reversed, but plasma triglycerides were not affected. Lipoprotein fractionation and cholesterol distribution analysis showed that CANA kept HDL-Cholesterol, LDL-Cholesterol, and IDL-Cholesterol levels steady while these lipoprotein species were increased in placebo- and insulin-treated control groups. CANA treatment of HF-STZ mice reduced post-heparin plasma lipoprotein lipase (LPL) activity at 2 (−40%) and 5 (−30%) weeks compared to placebo. Tissue-specific LPL activity following CANA treatment showed similar reduction. In summary, CANA prevented the total cholesterol increase in HF-STZ mice without effects on plasma lipids or lipoproteins, but did decrease LPL, implying a potential role of LPL-dependent lipoprotein metabolism in CANA action. These effects did not recapitulate the effect of SGLT2 inhibitors on lipids and lipoproteins in human, suggesting that a better murine T2DM model (such as the ApoB100 humanized CETP-overexpressing mouse) is needed next.
Keywords: SGLT2 inhibitors; lipoproteins; type 2 diabetes; lipoprotein lipase